SOCIAL CAPITAL AGRICULTURAL IN ASEAN 3 (INDONESIA, PHILIPPINES, AND THAILAND) - Antonette Kay P. Gabuya; Akkarawin Kareesor; Alvin Dwi Hariyono Dede Cristanto (UPT Penerbitan Universitas Jember)
As the ASEAN community has made agriculture as the main sector of economic development, the agriculture in developing countries could have important direct and indirect implications for economic development. “Social capital” refers to the relationships of trust, communication, and institution or cooperation that facilitate collective action in a community. This paper explores whether social capital might be a reason that can make agricultural production increase in ASEAN 3. Perhaps social capital can give contributions to the cooperatives for their fellow members as well as their leadership. Institutions are important because it is the agency or organization that carries out activity. In the community, several institutions can be found which has the function of regulating the behavior and attitudes of its citizens that is the guideline for them when having interactions with one another. The institution is a pattern of activity that is formed to meet the various needs of human life. Our preliminary result show that the social capital especially in the institutions in ASEAN 3 can make a good environment for agriculture as the main sector of economic development in ASEAN 3. This paper used a descriptive analysis for answering the preliminary as development of agriculture forwards is required revitalization of social capital and transformation of agriculture sectors.